Berenil Binds Tightly to Parallel and Mixed Parallel/Antiparallel G-Quadruplex Motifs with Varied Thermodynamic Signatures - Mikek, Clinton G. (ACS Omega, 2018)
[Image: see text] Diminazene, DMZ, (or berenil) has been reported as a tight binder of G-quadruplexes. G-Quadruplex structures are often located in the promotor regions of oncogenes and may play a regulatory role in gene expression based on the stability of the folding topology. In this study, attempts have been made to characterize the specificity of DMZ binding toward multiple G-quadruplex topologies or foldamers. Mutant sequences of the G-quadruplex forming promotor regions of several oncogenes were designed to exhibit restricted loop lengths and folding topologies. Circular dichroism was used to confirm the quadruplex topology of mutant BCL2, KRAS, and c-MYC sequences, human telomere (Na(+) and K(+)) G-quadruplexes and their complexes with DMZ and analogs thereof. Isothermal titration calorimetry was used to generate a complete thermodynamic profile (ΔG, ΔH, −TΔS) for the formation of DMZ and analog complexes with the target G-quadruplexes. DMZ binds to parallel and/or mixed parallel/antiparallel quadruplex DNA motifs with stoichiometries up to 8:1 and via three binding modes with varying affinities. In the case of the parallel G-quadruplexes, with the exception of the long-looped c-MYC mutant, the highest affinity binding event (mode 1) is driven by enthalpy. DMZ binding to the long-looped c-MYC mutant exhibits a very favorable entropy change in addition to a moderately favorable enthalpy change. Mode 1 binding to the antiparallel and mixed parallel/antiparallel hTel quadruplexes is also driven by favorable enthalpy changes. In all cases, the intermediate DMZ affinity binding (mode 2) is driven almost entirely by entropy, with small or unfavorable enthalpic contributions. The weakest binding event (mode 3) is also entropically driven with small or moderate enthalpic contributions.